Tren Riset Green Banking pada Perbankan Syariah di Indonesia: Analisis Bibliometrik Tahun 2019-2024 - Rafiqi, Iqbal; Sarah, Murniah (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2026)
This study aims to analyze trends in scientific publications related to the application of green banking in financing products within Islamic banking in Indonesia during the 2019–2024 period. Using a bibliometric analysis method based on Google Scholar data and mapping via VOSviewer software, this study evaluates 60 selected articles. The study results indicate a significant annual increase in publications, with a primary focus on integrating green banking principles into Islamic financing policies, their impact on profitability, and the role of technology in supporting green banking. Additionally, the study found that environmental sustainability, green financing, and digital transformation are the most dominant themes in the development of green banking research within Islamic banking. Bibliometric network analysis indicates a strong interconnection between the concepts of green finance, sustainable banking, and Islamic banking in supporting sustainable economic development. This study also identifies opportunities for further research related to the effectiveness of green banking implementation on the financial performance and social responsibility of Islamic banking. These findings contribute to the development of green finance literature in the Islamic finance sector and serve as a strategic reference for regulators and practitioners in implementing sustainable banking policies in the future.